1986
DOI: 10.1109/tps.1986.4316625
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Plasma Universe: II. The Formation of Systems of Galaxies

Abstract: Abstract-The model of the plasma universe, inspired by totally unexpected phenomena observed with the advent and application of fully three-dimensional electromagnetic particle-in-cell simulations to filamentary plasmas, consists of studying the interaction between fieldaligned current-conducting, galactic-dimensioned plasma sheets or filaments (Birkeland currents). In a preceding paper, the evolution of the interaction spanned some 108_109 years, where simulational analogs of synchrotron-emitting double radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Ideal models are sometimes too much simplified to reproduce the complicated galactic scenario but they are essential to show what are the actual competing forces. Corresponding author: battaner@ugr.es, estrella@ugr.es After the pioneering work of Peratt (1986) and Nelson (1988), the magnetic model has been considered in a series of papers. In a first model, Battaner et al (1992) showed that magnetic fields can provide a centripetal force.…”
Section: Introductionmentioning
confidence: 99%
“…Ideal models are sometimes too much simplified to reproduce the complicated galactic scenario but they are essential to show what are the actual competing forces. Corresponding author: battaner@ugr.es, estrella@ugr.es After the pioneering work of Peratt (1986) and Nelson (1988), the magnetic model has been considered in a series of papers. In a first model, Battaner et al (1992) showed that magnetic fields can provide a centripetal force.…”
Section: Introductionmentioning
confidence: 99%
“…Its new features (Buneman, 1994) are: (1) Poisson's equation and Fourier transforms have been eliminated by updating the fields locally from the curl equations and depositing the particle currents according to charge-conserving formulas (Villasenor and Buneman, 1992), (2) radiating boundary conditions are applied to the fields using a first order Lindman approximation (Lindman, 1975), (3) filtering is done locally, (4) localisation makes the code ideally suited to modern parallel machines which call for minimising data paths, (5) the code is in Fortran and fully transportable: modest versions run on PCs and on workstations. In the past, the TRISTAN code has successfully simulated large scale space plasma phenomena such as the formation of systems of galaxies (Peratt, 1986). The new version of the code (Buneman, 1994) has been applied to the study of the dynamics of low-/3 plasma clouds and the whistler wave driven by Spacelab 2 electron beam , electron-positron plasmas (Zhao et al 1994a,b) and current loop coalescence : Sakai et al, 1994.…”
mentioning
confidence: 99%
“…The author believes that the path whereby the self-magnetizing plasma forms the rotating bar and the spiral arms of the barred spiral galaxies has now been adequately illuminated and validated by the references provided in this paper (Bostick 1956(Bostick , 1957a(Bostick , 1958a(Bostick , 1958b(Bostick , 1986Peratt 1980Peratt , 1984Peratt , 1986.…”
Section: The Large Distribution Of Cosmic Plasmamentioning
confidence: 81%
“…
A 32-year-old hypothesis of the formation of barred-spiral galaxies (Bostick 1957(Bostick , 1958(Bostick , 1986Laurence, 1956) which become coherent-self-exciting homopolar generators has recently gained confirmative support from 3-D, particle-in-cell computer simulations (Nielsen et al 1979;Buneman et al 1980;Peratt et al 1980Peratt et al , 1984Peratt et al , 1986). Such galaxies should be able to convert an appreciable fraction, /, of the energy from their gravitationally-collapsing plasmas to coherently-increasing magnetic energy via their coherent, self-exciting, homopolar-generator action.
…”
mentioning
confidence: 99%